From pedagogy to quality assurance in education : an international perspective - Flavian, Heidi, 1965- (Bingley, U.K. : Emerald Publishing Limited, 2020)
In an increasingly global world, it is more important than ever that educators are equipped to respond to the needs of international student cohorts. This book is a fruitful resource for researchers, educators, and others, who wish to develop new approaches and educational models to contribute to the efficient process of learning.
Part I: Introduction -- Chapter 1: From Pedagogy to Quality Assurance in Education: An International Perspective -- Part II: Education and Schools -- Chapter 2.1: Critical Thinking Pedagogy and Quality Assurance in the United States -- Chapter 2.2: Proposal to Promote Quality of Education: A View from Spain -- Chapter 2.3: The Management and Assurance of Quality in Romanian Schools -- Chapter 2.4: Pedagogical Approaches and Initiatives for Educational Quality Assurance in Turkey -- Chapter 2.5: Congruence Between Pedagogical and Assessment Approaches: A Case of One Large Province in South Africa -- Part III: Special Education -- Chapter 3.1: Inclusion of Children with Special Needs as an Opportunity to Increase the Quality of Teaching in Israel -- Chapter 3.2: Inclusion, Diversity and Quality in the Mexican Educational Context: Perceptions of Teachers in the State of Sonora (Mexico) -- Part IV: Higher Education and Adult Education -- Chapter 4.1: Pedagogy and Quality Assurance in Thai Higher Education Institutions -- Chapter 4.2: Quality Assurance in Adult Education in Latvia -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Education -- Cross-cultural studies; Education -- Evaluation -- Cross-cultural studies; Quality assurance -- Cross-cultural studies; Comparative education; Education -- Educational Policy & Reform -- General; Organization & management of education